SHIFTING ON ORGANIZATIONAL MODEL IN RESPOND TO COVID-19 PANDEMIC : A STUDY IN THE IMPLEMENTATION OF THE 2020 POPULATION CENSUS (SP 2020) BY BADAN PUSAT STATISTIK PROVINSI KEPULAUAN BANGKA BELITUNG (Journal of Business and Management, 2021)
The year 2020 is the 7th time a population census has been carried out by the Central Statistics Agency. The presence of the COVID-19 pandemic in Indonesia at the beginning of 2020 caused several problems that disturbed the progress of the population census. Based on literature study, this research will apply McKinsey's 7s theory to diagnose and identify this shift. The general model of planned change by Thomas G. Cumming and Christopher G. Worley is the basic model of the process and methodology of this research. To measure the level of effectiveness of the shift that has occurred, the author will make a comparison with the objective of implementing the 2020 Population Census itself. The results are BPS Prov. Kep. Bangka Belitung made major adjustments to the indicators of strategy, staffing, system and structure. Not too many big changes were made to the style indicator, and only minor changes to the skill indicator. As for the shared value indicator, no adjustments were made.Keywords: Population Census, Covid-19 Pandemic, Organizational Model, 7s Mckinsey, planned change